Hantavirus circulation in Oligoryzomys Flavescens rodents of Buenos Aires City, Argentina - Hercolini, C. (2018)
Hantavirus pulmonary syndrome (HPS) is a zoonotic disease. The main cause in Argentina is Andes virus. Oligoryzomys flavescens (Sigmodontinae) was identify as one of the HPS reservoir. The objective of this research was to estimate the seroprevalence of hantavirus in O. flavescens in Buenos Aires City. We set rodents live trapping in three parklands and one ecological reserve in Buenos Aires City in order to screen hantavirus Andes infected rodents. A total of 286 rodents were captured, O. flavescens was the most frequently captured species (49.65%). Positive serology for Andes virus (Lechiguanas genotype) was found in O. flavescens in one site studied (seroprevalence = 6.62%) and we found the host in other two parks within the City. The present study confirms the presence of rodents infected with Andes virus in Buenos Aires City, which implies transmission risk in an urban environment.\n